Serum polyunsaturated fatty acids in infancy are associated with body composition in adolescence. Issue 11 (19th May 2020) - Flannagan, Kerry; Gahagan, Sheila; Das, Arun; Burrows, Raquel; Lozoff, Betsy; Villamor, Eduardo
Summary: Background: Polyunsaturated fatty acids (PUFA) have been related to the development of adiposity. N‐3 PUFA appears to be protective against obesity risk, while n‐6 PUFA may be associated with greater adiposity. However, most studies have been conducted among adults. The role of PUFA in infancy is unknown. Objective: To examine associations of serum PUFA at age 1 year with age‐ and sex‐adjusted body mass index Z score (BMIZ) change through age 16 years and body composition at 16 years. Methods: We quantified serum PUFA in 636 Chilean infants aged 1 year. We measured BMIZ at ages 1, 5, 10 and 16 years, and body composition by dual energy X‐ray absorptiometry at 16 years. We estimated differences in 1‐ to 16‐years BMIZ change between PUFA quartiles from multivariable linear mixed models with restricted cubic splines. At 16 years, we estimated differences in total fat mass (ToFM), truncal fat mass (TrFM), total lean mass (TLM), percent total fat mass (%ToFM) and percent truncal fat mass (%TrFM) between PUFA quartiles using linear regression. Results: PUFA were not associated with BMIZ change. Alpha‐linolenic acid (ALA) was positively associated with TrFM ( P = .03) and %TrFM ( P < .0001) at 16 years while eicosapentaenoic acid (EPA) was inversely associated with %TrFM ( P = .001). Docosapentaenoic acid (DPA) was positively associated with ToFM ( P = .01), TrFM ( P = .009), %ToFM ( P = .02) and %TrFM ( P = .02). Gamma‐linolenic acid (GLA) and the Δ6‐desaturase (D6D) activity index were each positively, linearly associated with ToFM, TrFM and %ToFM. The Δ5‐desaturase (D5D) activity index was inversely associated with %TrFM ( P = .04). Conclusions: ALA, DPA, GLA and the D6D index at 1 year of age were positively associated with adiposity at age 16 years, while EPA and the D5D index were inversely associated with central adiposity. Our results related to EPA and desaturase indices are in agreement with limited prior studies.